Pengaruh Stimulus Inovasi terhadap Kinerja Inovasi Dengan Kapabilitas Inovasi sebagai Mediator: Analisis Empiris Pada Industri Batik - Jonner Simarmata (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
MSMEs need to innovate, especially product innovation and process innovation to increase their competitiveness in facing the onslaught of various external changes. This article aims to inform the role of innovation capability in mediating the relationship between innovation stimulus and innovation performance. For this purpose, a sample of 120 people, namely Jambi batik industry entrepreneurs and craftsmen, has been distributed. The collected data were analyzed using the regression method with a mediation approach. The results of the analysis show that (1) innovation stimulus is positively correlated with innovation performance, and (2) innovation capability is proven to mediate the relationship between the two variables. The results of this study suggest that MSME actors, especially those engaged in the batik industry, increase their innovation capabilities through increasing and tightening the innovation stimulus in order to achieve high innovation performance.